1965
DOI: 10.1002/ar.1091520214
|View full text |Cite
|
Sign up to set email alerts
|

The weight and thickness of the two ventricular walls in the newborn dog heart

Abstract: The weight and thickness of the two ventricular walls of the heart were measured in 80 newborn puppies. These puppies were born in the dog colony, the descendants of a typical heterogeneous collection of dogs, for student use in the laboratory.The hearts of these dogs average 2.07 gm in weight. The left ventricular wall is slightly heavier and also slightly more variable in weight than the right wall. The two free ventricular walls comprise 56% of the weight of the entire heart. The ratio of the weight of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1967
1967
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…study, it appears that the heart ventricles grow similarly in children with hydrocephalus and in normal children, and that the presence of a cerebro-cardiac shunt, though presenting frequent embolic/thrombotic lesions in the lungs, does not appear, at least over a period of a few (less than five) years, to induce changes in the heart suggesting the development of significant pulmonary hypertension. The postnatal changes in weight of the ventricles in this study show the accelerated increase in growth of the left heart after birth as in our own previous study (Emery and Mithal, 1961) and in the older literature (Miller, 1883;Falk, 1901) and in dogs (Latimer, 1965). The apparent actual diminution in weight of the right ventricle suggested by Keen (1955) and Recavarren and Arias-Stella (1964) is probably due to an unfortunate selection of material and method of study.…”
Section: Resultssupporting
confidence: 84%
“…study, it appears that the heart ventricles grow similarly in children with hydrocephalus and in normal children, and that the presence of a cerebro-cardiac shunt, though presenting frequent embolic/thrombotic lesions in the lungs, does not appear, at least over a period of a few (less than five) years, to induce changes in the heart suggesting the development of significant pulmonary hypertension. The postnatal changes in weight of the ventricles in this study show the accelerated increase in growth of the left heart after birth as in our own previous study (Emery and Mithal, 1961) and in the older literature (Miller, 1883;Falk, 1901) and in dogs (Latimer, 1965). The apparent actual diminution in weight of the right ventricle suggested by Keen (1955) and Recavarren and Arias-Stella (1964) is probably due to an unfortunate selection of material and method of study.…”
Section: Resultssupporting
confidence: 84%
“…The closing of the ductus arteriosus after birth results in only smaller circulation being pumped by the right ventricle, so the systemic load moves to the left ventricle. This process is seen by increasing the wall thickness of the left ventricle faster than the right ventricle (Latimer 1965). The left being thicker, is more powerful to pump the blood with more force and more rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…in a study of 21 canine foetal pups, found that the right ventricle exceeded that of the left ventricle at the midventricular wall level. Latimer (1965), however, found that in newborn puppies, the wall of the left ventricle was slightly thicker than that of the right ventricle and the ratio of the thickness of the left to the right ventricular wall was 1.036. Matthiesen and Deegen (1976) on the equine foetal and newborn heart, reported that the ratio of left to right ventricular wall thickness changed from 1.4 (five to eight months of foetal age) to 1.5 (perinatal period) and to 2.2 (over six months of newborn age).…”
Section: Equation*mentioning
confidence: 92%
“…This finding may result from the slower growth of the atria than the ventricles. The relative thickness of the walls of the left and right ventricles in prenatal and newborn dogs has been studied by Williams, Powers and Hamlin (1979) and Latimer (1965). Williams et a1 (1979).…”
Section: Equation*mentioning
confidence: 99%